Categorization of the gut microbiota: enterotypes or gradients? - Jeffery, Ian B.; Claesson, Marcus J.; O'Toole, Paul W.; Shanahan, Fergus (Nature reviews. Microbiology, 2012)
Grouping the microbiota of individual subjects into compositional categories, or enterotypes, based on the dominance of certain genera may have oversimplified a complex situation. Grouping the microbiota of individual subjects into compositional categories, or enterotypes, based on the dominance of certain genera may have oversimplified a complex situation.